2018
DOI: 10.3390/ijms19092788
|View full text |Cite
|
Sign up to set email alerts
|

Standards for Deriving Nonhuman Primate-Induced Pluripotent Stem Cells, Neural Stem Cells and Dopaminergic Lineage

Abstract: Humans and nonhuman primates (NHP) are similar in behavior and in physiology, specifically the structure, function, and complexity of the immune system. Thus, NHP models are desirable for pathophysiology and pharmacology/toxicology studies. Furthermore, NHP-derived induced pluripotent stem cells (iPSCs) may enable transformative developmental, translational, or evolutionary studies in a field of inquiry currently hampered by the limited availability of research specimens. NHP-iPSCs may address specific questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…It is generally recognized that the reprogramming of NHP cells is less efficient in comparison to the well-established human reprogramming techniques [ 31 , 32 ], although this has not been systematically quantified so far. For instance, it has been demonstrated that marmoset monkey iPSC generation required five or even six reprogramming factors [ 33 , 34 , 35 ], and marmoset cell reprogramming with the four Yamanaka factors was successful only after around 100 days [ 36 ]. In agreement with these observations, also low efficiency of macaque iPSC line generation has been recognized [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally recognized that the reprogramming of NHP cells is less efficient in comparison to the well-established human reprogramming techniques [ 31 , 32 ], although this has not been systematically quantified so far. For instance, it has been demonstrated that marmoset monkey iPSC generation required five or even six reprogramming factors [ 33 , 34 , 35 ], and marmoset cell reprogramming with the four Yamanaka factors was successful only after around 100 days [ 36 ]. In agreement with these observations, also low efficiency of macaque iPSC line generation has been recognized [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…As study models, NH-primates are highly attractive due to longevity, behavioral, anatomical, genetic, physiological, and immunological similarities with humans [5,[7][8][9][10]. Over the past decades, NH-primates have been used on studies and research to prevent or cure human conditions, through the development of vaccines and drugs or treatment for cancer, diabetes, obesity, Parkinson's and other neurodegenerative, respiratory and cardiovascular diseases [4,5,11,12], as well as methods to prevent mother-fetus transmission of diseases such as HIV [13], amongst other conditions and illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…Amongst NH-primates, they include but are not limited to the rhesus [27]; drill [28]; cynomolgus monkey [29,30]; marmoset [31]; baboon [32]; orangutans [33]; Japanese macaque [34]. These cells were mainly generated from fibroblasts and integrative methods, but more recently, they were produced through non-integrative methods, such as Sendai-virus and episomal vectors [10,[35][36][37]. NH-primate-derived iPSCs have been used in research related to or as models for neurological [38][39][40][41], cardiac [36,42,43], reproductive [44], hematopoietic conditions [37,45], transplantation and grafting [30,46] and others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…iPS cells have been generated from fetus liver‐, newborn skin‐ and adult bone marrow‐derived cells by introducing reprogramming factors using retrovirus or lentivirus (Tomioka et al, ; Wiedemann et al, ; Wu, Zhang, Mishra, Tardif, & Hornsby, ). More recently, iPS cells were generated without altering the genomic sequence using an excisable transposon vector and episomal vector from postnatal and adult skin cells, respectively (Debowski et al, ; Yang et al, ). In humans, RNA‐based methods are increasingly applied in the integration‐free generation of iPS cells, as they can lower the risk of introducing mutation (Anokye‐Danso et al, ; Mandal & Rossi, ; Poleganov et al, ; Rohani et al, ; Warren et al, ; Yoshioka et al, ).…”
Section: Introductionmentioning
confidence: 99%